2007
DOI: 10.1371/journal.pone.0000689
|View full text |Cite
|
Sign up to set email alerts
|

GDNF Secreting Human Neural Progenitor Cells Protect Dying Motor Neurons, but Not Their Projection to Muscle, in a Rat Model of Familial ALS

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a fatal, progressive neurodegenerative disease characterized by rapid loss of muscle control and eventual paralysis due to the death of large motor neurons in the brain and spinal cord. Growth factors such as glial cell line derived neurotrophic factor (GDNF) are known to protect motor neurons from damage in a range of models. However, penetrance through the blood brain barrier and delivery to the spinal cord remains a serious challenge. Although there may be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
246
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(265 citation statements)
references
References 60 publications
15
246
1
3
Order By: Relevance
“…A similar effect was observed following intracerebral transplantation of NPCs after ischemia/reperfusion injury in mice [155]. In a Parkinson's disease model, transplanted NPCs rescued endogenous dopaminergic neurons of the mesostriatal system [156], and in models of amyotrophic lateral sclerosis transplanted NPCs prevented motor neurons from dying [157][158][159]. Transplantation experiments in models of spinal cord injury have provided several insights to the basic biological mechanisms by which the various types of precursor cells exhibit their therapeutic functions (for more detail see Einstein and Ben-Hur [160]).…”
Section: Trophic Support By Transplanted Precursor Cellsmentioning
confidence: 55%
“…A similar effect was observed following intracerebral transplantation of NPCs after ischemia/reperfusion injury in mice [155]. In a Parkinson's disease model, transplanted NPCs rescued endogenous dopaminergic neurons of the mesostriatal system [156], and in models of amyotrophic lateral sclerosis transplanted NPCs prevented motor neurons from dying [157][158][159]. Transplantation experiments in models of spinal cord injury have provided several insights to the basic biological mechanisms by which the various types of precursor cells exhibit their therapeutic functions (for more detail see Einstein and Ben-Hur [160]).…”
Section: Trophic Support By Transplanted Precursor Cellsmentioning
confidence: 55%
“…The strategy of using stem cells as a drug delivery system for brain tumors has been applied in the rodent for >10 years [34]. Additional studies showed that the delivery of glial cell line-derived neurotrophic factor through engineered human neural progenitor cells improved neurons survival and function in the rodent models of Huntington's disease, Parkinson's disease, and amyotrophic lateral sclerosis [35][36][37][38]. Likewise, transplantation of MGE cells into the epileptic cortex has been proposed as a cell-based therapy for medically intractable epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, since motor nerve terminals, terminal Schwann cells and neuromuscular transmission appear largely normal in R6/2 mice , denervation, paralysis or muscle atrophy would appear to be sufficient to provoke the kranocyte cell reaction; but the reaction of these cells is evidently not sufficient to trigger the subsequent Schwann cell reaction in this disease model. It would be interesting to know the disposition and fate of kranocytes in other models of neuromuscular disease, particularly models of amyotrophic lateral sclerosis, where neuromuscular synaptic degeneration is among the earliest signs of disease (Fischer et al, 2004;Schaefer et al, 2005;Pun et al, 2006;Suzuki et al, 2007).…”
Section: Developmental and Plasticity Of Kranocytesmentioning
confidence: 99%